2019
DOI: 10.24925/turjaf.v7i2.258-265.2238
|View full text |Cite
|
Sign up to set email alerts
|

Farklı Besin Solüsyonlarının Yüzen Su Kültüründe Rokanın Verim ve Kalite Özelliklerine Etkileri

Abstract: This study was conducted in styrofoam trays placed on an aerated nutrient solution in vats in order to determine the effect of different nutrient solutions on rocket plant growth, yield and quality. Seeds of Bengi F1 rocket cultivar were sown into peat as inserting each seed to each hole (17 ccs) of trays with 210 cells (957 plant m-2). Following germination in the germination chamber, seedling trays were moved to a climate controlled greenhouse for adaptation. After emergence, the seedlings were transferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In another study examining the color values in arugula, it was reported that L * values ranged from 42.02 to 43.50, a * values from −15.05 to −19.90, b * values from 19.86 to 22.98 (Tuncay, 2011). It was determined that the L * values in arugula were between 42.68 and 43.83, a * values between −16.74 and −17.77, and b * values between 24.91 and 26.77 (Oztekin et al., 2019). Although the results for arugula samples demonstrated in Table 1 in the current study were similar to the literature (Colonna et al., 2016; Oztekin et al., 2019) in terms of L * and b * values, it was found that they were between the range of −2.2 (Colonna et al., 2016) and −19.90 (Tuncay, 2011) in terms of a * value.…”
Section: Resultsmentioning
confidence: 99%
“…In another study examining the color values in arugula, it was reported that L * values ranged from 42.02 to 43.50, a * values from −15.05 to −19.90, b * values from 19.86 to 22.98 (Tuncay, 2011). It was determined that the L * values in arugula were between 42.68 and 43.83, a * values between −16.74 and −17.77, and b * values between 24.91 and 26.77 (Oztekin et al., 2019). Although the results for arugula samples demonstrated in Table 1 in the current study were similar to the literature (Colonna et al., 2016; Oztekin et al., 2019) in terms of L * and b * values, it was found that they were between the range of −2.2 (Colonna et al., 2016) and −19.90 (Tuncay, 2011) in terms of a * value.…”
Section: Resultsmentioning
confidence: 99%